The COVID-19 Pandemic and the Obsessive-Compulsive Phenomena, in the General Population and among OCD Patients: A Systematic Review - Malas, Olga; Tolsá, Maria-Dolores (European Journal of Mental Health, 2022)
Introduction: An increase in obsessive-compulsive disorder (OCD) was predicted as a consequence of the COVID-19 pandemic and the measures established for controlling it. Aims: This review seeks to analyze the relationship between the COVID-19 pandemic and obsessive-compulsive disorder (OCD), and in particular the pandemic’s effect on the prevalence of obsessive-compulsive (OC) symptoms, predisposing factors, interventions carried out, their effectiveness and the proposal of interventions in future situations similar to the one studied. Methods: For this purpose, a systematic review of empirical articles, published from November 2019 to June 2022, is carried out, following the PRISMA methodology. The review was registered in Open Science Forum [10.17605/OSF.IO/DV8GZ]. Results: The studies indicated an increase in the prevalence of OC symptoms in the general population, as well as new obsessions, relapses, and/ or worsening of the pre-existing symptoms in patients with OCD mainly related to contamination obsessions and cleaning and hand washing compulsions. Predisposing factors are being younger, low resilience, low social support, the presence of previous contamination symptoms, overexposure to news about COVID-19, the previous severity and aggressiveness of OC symptomatology, and the absence or lack of treatment adherence. The combined use of pharmacological treatment, cognitive-behavioral therapies, teaching skills to reinforce resilience, and training in coping strategies will be recommended. Conclusions: The data obtained can be used as a basis for future OCD prevention plans in crises similar to the one studied.